A HIGH-RESOLUTION RECORD OF HOLOCENE RAINFALL VARIATIONS FROM THE WESTERN CHINESE LOESS PLATEAU: ANTIPHASE BEHAVIOUR OF THE AFRICAN/INDIAN AND EAST ASIAN SUMMER MONSOONS - Maher B.A.; Hu M. (My University, 2006)
Tropical monsoons are key mechanisms for transfer of heat and moisture to higher latitudes. Here we present a high-resolution, terrestrial proxy summer monsoon record for the southeast Asian monsoon, from a rapidly accumulating Holocene loess/soil sequence in the western Chinese Loess Plateau. We use magnetic and clastic grain size proxies to make quantitative estimates of Holocene rainfall and identify variations in winter monsoon intensity. Our record reveals cyclical millennial and multimillennial rainfall changes. As with the northwest African/southwest Asian monsoon records, a short arid interval at ~ 12.5 to 11.5 ka BP (the Younger Dryas) and subsequent summer monsoon intensification are recorded. However, at 6 ka BP, the southeast Asian summer monsoon weakened, when the northwest African/ southwest Asian monsoons strengthened, and then, from ~ 5 ka BP, intensified, when northwest Africa/ southwest Asia became dry. These antiphase monsoonal relationships may reflect competition between sea-surface temperature changes and solar forcing. The intensity of the southeast Asian winter monsoon intensified from ~ 9 ka BP onwards, varying in its phase relationships with summer monsoon intensity. After ~ 2.25 ka BP, extreme climatic instability is indicated by both climate proxies. © 2006 Edward Arnold (Publishers) Ltd.
Keywords: ANTIPHASING; CHINA; EAST ASIAN MONSOON; HOLOCENE; INDIAN MONSOON; LOESS; LOESS PLATEAU; MONSOON INTENSITY; PALAEOSOLS; RAINFALL VARIABILITY; TROPICAL CLIMATE; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен